2017
DOI: 10.1177/2167702617696511
|View full text |Cite
|
Sign up to set email alerts
|

Bleak Present, Bright Future: Online Episodic Future Thinking, Scarcity, Delay Discounting, and Food Demand

Abstract: Obesity is associated with steep discounting of the future and increased food reinforcement. Episodic future thinking (EFT), a type of prospective thinking, has been observed to reduce delay discounting (DD) and improve dietary decision making. In contrast, negative income shock (i.e., abrupt transitions to poverty) has been shown to increase discounting and may worsen dietary decision-making. Scalability of EFT training and protective effects of EFT against simulated negative income shock on DD and demand for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
186
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 149 publications
(208 citation statements)
references
References 103 publications
18
186
3
1
Order By: Relevance
“…To generate episodic events, participants used a self-guided generation task (Sze et al in press) similar to staff-guided tasks used in previous studies (Daniel et al 2013; O’Neill et al 2016; Stein et al 2016; Snider et al 2016). EFT participants generated personalized future events that they were looking forward to and could vividly imagine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To generate episodic events, participants used a self-guided generation task (Sze et al in press) similar to staff-guided tasks used in previous studies (Daniel et al 2013; O’Neill et al 2016; Stein et al 2016; Snider et al 2016). EFT participants generated personalized future events that they were looking forward to and could vividly imagine.…”
Section: Methodsmentioning
confidence: 99%
“…In laboratory-based studies, EFT robustly reduces delay discounting in overweight and obese participants (Daniel et al 2013; Sze et al in press) and produces concomitant reductions in both ad-libitum energy intake (Daniel et al 2013) and the relative reinforcing efficacy of unhealthy foods (Sze et al in press). Adapting these methods for use in natural settings has shown that EFT holds promise as a targeted weight loss treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EFT has previously been shown to decrease DD in individuals with alcholol use disorder [32], smokers [33], as well as normal weight, overweight, and obese populations [34,35]. Consistent with the reinforcer pathology concept, EFT may reduce the demand for hypothetical drinks [32], self-administration of cigarettes [33], and self-administration and valuation of highly palatable snacks in overweight and/or obese adults and children [35,36]. Conversely, when smokers or obese individuals were exposed to a scarcity scenario (drastic income reduction), they discounted more (valued the future less) and drug craving and valuation of preferred foods increased [36].…”
Section: Reinforcer Pathology As a Prototype ‘Biomarker’mentioning
confidence: 97%
“…Consistent with the reinforcer pathology concept, EFT may reduce the demand for hypothetical drinks [32], self-administration of cigarettes [33], and self-administration and valuation of highly palatable snacks in overweight and/or obese adults and children [35,36]. Conversely, when smokers or obese individuals were exposed to a scarcity scenario (drastic income reduction), they discounted more (valued the future less) and drug craving and valuation of preferred foods increased [36]. One important future area of research would be to extend this model to address the ‘dark side’ of addiction, such as assessing the consequence of withdrawal.…”
Section: Reinforcer Pathology As a Prototype ‘Biomarker’mentioning
confidence: 99%